Formalizing Alumni Mentoring in Social Work Education: Lessons Learned From a Three-Year Program Evaluation. (3rd April 2022) - Skrzypek, Candra; Diebold, Josal; Kim, Wooksoo; Krause, Denise
ABSTRACT: Alumni mentoring in social work allows students to connect with experienced practitioners in a nonevaluative context and for alumni to strengthen university connections. This study describes and evaluates one established student–alumni mentoring program. Pretest (n=277) and posttest (n=153) data were collected from participants across 3 years. Results indicated that the mentoring relationship between alumni and students was most often fulfilled through informal meetings and the teaching of life skills, followed by professional and career development. More than one-third of students identified the program as helpful to their academic success, while the majority of alumni felt the program had potential for strengthening school–community relationships. Lessons learned and implications of alumni mentoring programs in social work education are discussed.